PENDEKATAN PRAGMATIK DALAM BUKU PERNAH TENGGELAM KARYA FUADH NAIM - Irfan Juhari (Universitas Maritim AMNI Semarang, 2022)
The book Ever Drowned by Fuadh Naim tells the story of the life journey of the writer who was an ex-fanboy until he migrated after contemplating. Using a pragmatic approach, the analysis of this book seeks to convey a certain goal to the reader. The purpose of this research is to describe the book Ever Drowned by Fuadh Naim using a pragmatic approach. The research method used is descriptive qualitative method. While the results of this research are for readers to gain deeper insight into the world of fanboys and everything related to them. Not only that, readers can also take a lot of lessons from the life story of a writer who managed to move without having to immediately stay away from Korean things.